EDUKASI MANFAAT AROMATERAPI LAVENDER TERHADAP KUALITAS TIDUR PADA IBU HAMIL - sihaloho, wilfa muslimah; Krisna, Putri; Damanik, Yunita Syahputri (INSTITUT KESEHATAN DELI HUSADA, 2025)
Especially with fetal abnormalities, pregnant women rarely get basic quality sleep. Critical well-being and cardiovascular problems, including hypertension, may arise from poor sleep quality during pregnancy. Treatments based on lavender aroma are one of the many options for improving the quality of sleep for pregnant women. Community service plays an important role in improving the quality of maternal health through improving the quality of sleep by providing education about the benefits of lavender aroma therapy for pregnant women. Through this educational activity, pregnant women can benefit from lavender aroma therapy to improve the quality of their sleep.